Lifetime Spectroscopy A Method of Defect Characterization in Silicon for Photovoltaic Applications - Rein, Stefan (Springer Series in Materials Science, 2005)
Lifetime spectroscopy is one of the most sensitive diagnostic tools for the identification and analysis of impurities in semiconductors. Since it is based on the recombination process, it provides insight into precisely those defects that are relevant to semiconductor devices such as solar cells. This book introduces a transparent modeling procedure that allows a detailed theoretical evaluation of the spectroscopic potential of the different lifetime spectroscopic techniques. The various theoretical predictions are verified experimentally with the context of a comprehensive study on different metal impurities. The quality and consistency of the spectroscopic results, as explained here, confirms the excellent performance of lifetime spectroscopy.